Some problems of the development of new national standards for methods of platinum metals and alloys analysis. - L. P. Zhitenko; E. G. Khomutova; O. I. Ostanina (Тонкие химические технологии)
A review of the currently effective Russian national standards for methods of platinum metal and alloy analysis has been made, many of the standards being obsolete as for their content and the analytical procedures used. Some problems of the development of the new national standards have been described and the way of problem solving has been suggested.